O-63 Pesticide exposure and health effects among greenspace workers. (14th March 2023) - Graaf, Lucie de; Bureau, Mathilde; Boulanger, Mathilde; Budzinski, Hélène; Lebailly, Pierre; Baldi, Isabelle
Abstract : Introduction: Greenspace workers are exposed to many occupational hazards, including pesticides. Few epidemiological studies have been conducted among these workers, most of them using rough exposure parameters. Thus, improvement in exposure assessment is crucial to expand our knowledge on greenspace workers' health. Our objectives were to i) define past pesticide exposures in greenspace workers and ii) characterise present exposure levels in real work conditions. This project has received funding from the French National Research Agency. Methods: To identify pesticides used in the past, we explored various historical data sources that enabled to increment the crop-exposure matrix PESTIMAT (France) with molecules used in greenspaces since 1950. For each molecule, the probability, the frequency and the intensity of use were estimated on an annual basis. To characterise present exposures, field studies in real work conditions were conducted among municipal workers and gardeners in 2011 and in a plant nursery in 2022 during treatment tasks. Dermal exposure was assessed using patches placed onto the skin and cotton gloves. Detailed information on the tasks were collected to identify determinants of exposure. Results: Fifty active ingredients used in greenspaces (including pyrethrinoids, organochlorines, carbamates, dinitroanilines, etc.) have been added into PESTIMAT to date. The field studies were conducted among 24 municipal workers applying glyphosate with knapsacks and among six plant nursery workers applying insecticides (bifenazate, azoxystrobine and difenoconazole), fungicides (boscalid and pyraclostrobine) and the herbicide glyphosate. Analyses of dosimeters are ongoing and will be linked with the detailed characteristics we collected on workers, tasks, conditions of work, equipment and practices. Conclusion: The data we generated on the types of molecules and exposure levels will help to build metrics for pesticide exposures in greenspace workers, usable in epidemiological studies. Associations between the use of specific active ingredients and cancer occurrence will be studied in existing cohorts.